2019
DOI: 10.1029/2019gl084965
|View full text |Cite
|
Sign up to set email alerts
|

Foraminifera Trace Anthropogenic CO2 in the NW Atlantic by 1950

Abstract: The Northwest Atlantic is a region of major climate change over the twentieth century, affected by the weakening of the Atlantic meridional overturning circulation. To assess whether the ability of this region to absorb anthropogenic CO 2 has been impacted by this change, we present the region's first long-term carbon isotope (δ 13 C) time series of fossil foraminifera spanning the past 4,000 years. These records reveal an unprecedented negative δ 13 C excursion driven by anthropogenic CO 2 penetration into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…The 13 C-depleted carbon has been widely reported in coral skeleton and sclerosponge (Druffel and Benavides, 1986;Swart et al, 1996a;Swart et al, 1996b;Swart et al, 2010;Al-Rousan and Felis, 2013;Hou et al, 2019;Liu et al, 2021) and planktonic foraminifera (Al-Rousan et al, 2004;Black et al, 2011;Xu et al, 2014;Mellon et al, The light gray symbol shows all the δ 13 C of planktonic foraminifers in this study, and the LOESS fit represent the situation in the mid-low latitude Pacific Ocean. The orange, purple, and light blue lines represent the situation of planktonic foraminifera in the Atlantic Ocean at low, mid, and high latitudes, respectively (adopted from Black et al, 2011;Mellon et al, 2019;Simon et al, 2020). The δ 13 C axis of these three data sets was shifted to facilitate comparison with our data.…”
Section: The δ 18 O Variability In Core Samplessupporting
confidence: 51%
See 4 more Smart Citations
“…The 13 C-depleted carbon has been widely reported in coral skeleton and sclerosponge (Druffel and Benavides, 1986;Swart et al, 1996a;Swart et al, 1996b;Swart et al, 2010;Al-Rousan and Felis, 2013;Hou et al, 2019;Liu et al, 2021) and planktonic foraminifera (Al-Rousan et al, 2004;Black et al, 2011;Xu et al, 2014;Mellon et al, The light gray symbol shows all the δ 13 C of planktonic foraminifers in this study, and the LOESS fit represent the situation in the mid-low latitude Pacific Ocean. The orange, purple, and light blue lines represent the situation of planktonic foraminifera in the Atlantic Ocean at low, mid, and high latitudes, respectively (adopted from Black et al, 2011;Mellon et al, 2019;Simon et al, 2020). The δ 13 C axis of these three data sets was shifted to facilitate comparison with our data.…”
Section: The δ 18 O Variability In Core Samplessupporting
confidence: 51%
“…Although there were isotopic offsets between precipitated calcium carbonate shells and the ambient seawater, Mellon et al (2019) have indicated that decline trends of the δ 13 C recorded by different species of foraminiferal were still consistent. To compare δ 13 C among different planktonic foraminiferal records, data published in previous studies were digitalized and plotted with the long-term variability of measured planktonic δ 13 C in this study (Figure 4E).…”
Section: The δ 18 O Variability In Core Samplesmentioning
confidence: 94%
See 3 more Smart Citations